Pemakaian Bahasa pada Inskripsi Makam Raja-Raja di Kalimantan Bagian Timur - Bambang Sakti Wiku Atmojo; Saefuddin Saefuddin; Agus Yulianto (PANALUNGTIK, 2022)
The tombs of the kings in the eastern part of Kalimantan are spread over six districts in three provinces. The figures buried were the king, son of the king, queen, prime minister and other members of the royal family. This study aims to determine the letters and language used to write inscriptions on these tombs. The data collection method used is an exploratory survey, documented using photographs, drawings and maps or plans. The results showed that most of the graves were inscribed, some using Arabic letters, some using Bugis letters and some using Latin letters. The languages ​​spoken include Arabic, Malay, and Bugis. These inscriptions can be categorized as calligraphy using media of wood, stone and metal. Regarding the use of these languages, it can be concluded that there is a connection with various things, including the people who inhabit the area, the blend of local culture with foreign culture, and the contents of the inscriptions. The use of the Malay language shows that the language is used widely in various regions of the archipelago, the use of the Bugis language is related to the existence of the Bugis people who inhabit the area, while the Arabic language is used to display monotheistic sentences, verses of the Koran and the title of the Prophet Muhammad.